Obstructive sleep apnea in the hemodialysis population: are clinicians putting existing scientific evidence into practice? - Burkhalter, David Andri; Cartellá, Antonio; Cozzo, Domenico; Ogna, Adam; Forni Ogna, Valentina (Frontiers in Nephrology, 2024)
IntroductionHemodialysis (HD) populations have a high prevalence of Obstructive Sleep Apnea (OSA), which was specifically linked with fluid overload. HD fluid management targeting a low dry weight was shown to reduce OSA severity, opening to novel therapeutic options. We assessed nephrologists’ awareness of OSA diagnosis in HD patients and whether they integrate the current knowledge into their fluid management strategy.Material and methodsWe performed a multicenter, cross-sectional study between July 2022 and July 2023, screening all HD patients of four HD units, and included those with confirmed OSA. We collected anthropometric parameters and fluid status from electronic dossiers. Predialysis fluid overload was measured by multifrequency bioelectrical impedance (BCM®). Nephrologists were asked to identify patients with known OSA, without consulting medical dossiers. The fluid management of patients identified as “OSA positive” was compared to that of patients misclassified as “OSA negative”.ResultsAmong 193 HD patients, 23.0% (n=45) had confirmed OSA. The mean age was 76.0 ± 7.5 years, 82.2% were men. Only 60% were correctly identified as “OSA positive” by nephrologists; 14.7% of patients on CPAP were identified. BMI was the only factor associated with correct OSA identification. The predialysis fluid overload tended to be greater in “OSA positive” patients than in the “OSA negative” patients (2.2 ± 1.4 kg vs 1.5 ± 1.3 kg; p=0.08), but there was no difference in postdialysis achievement of dry weight between the groups (residual overweight 0.2 ± 1.0 kg and 0.1 ± 0.7 kg; p= 0.672).ConclusionsOur study suggests that the application of scientific evidence to the management of OSA in dialysis patients is not systematic. However, nephrologists have attempted to strictly achieve dry weight in all patients, regardless of OSA status. Sensibilization of nephrologists on the clinical and diagnostic peculiarities of OSA in HD patients may improve OSA diagnosis and therapeutic care.